Toll-Like Receptor 4, but Not Neutrophil Extracellular Traps, Promote IFN Type I Expression to Enhance Th2 Responses to Nippostrongylus brasiliensis - Pellefigues, Christophe; Tang, Shiau-Choot; Schmidt, Alfonso; White, Ruby F.; Lamiable, Olivier; Connor, Lisa M.; Ruedl, Christiane; Dobrucki, Jurek; Le Gros, Graham; Ronchese, Franca (Frontiers in Immunology, 2017)
The induction of Th2 responses is thought to be multifactorial, and emerge from specific pathways distinct from those associated with antagonistic antibacterial or antiviral Th1 responses. Here, we show that the recognition of non-viable Nippostrongylus brasiliensis (Nb) in the skin induces a strong recruitment of monocytes and neutrophils and the release of Neutrophil Extracellular Traps (NETs). Nb also activates TLR4 signaling with expression of Ifnb transcripts in the skin and the development of an IFN type I signature on helminth antigen-bearing dendritic cells in draining lymph nodes. Co-injection of Nb together with about 10,000 Gram-negative bacteria amplified this TLR4-dependent but NET-independent IFN type I response and enhanced the development of Th2 responses. Thus, a limited activation of antibacterial signaling pathways is able to boost antihelminthic responses, suggesting a role for bacterial sensing in the optimal induction of Th2 immunity.